2022
DOI: 10.1159/000523902
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Serum miR-138-5p and Its Clinical Significance in Patients with Acute Cerebral Infarction

Abstract: <b><i>Introduction:</i></b> Acute cerebral infarction (ACI) occurs with the involvement of differential expression of microRNAs. The study detected the expression pattern of miR-138-5p in the serum of ACI cases and evaluated its clinical significance, in an attempt to provide some guidance for the treatment and daily nursing of patients with ACI clinically. <b><i>Methods:</i></b> Levels of miR-138-5p in the serum of ACI patients and healthy controls (HCs) were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The pathogenesis of CI is complex, and it has been shown that it is related to excessive production of free radicals, the toxic effect of excitatory amino acids, intracellular calcium overload, inflammatory response, and autophagy [21][22][23]. miRNAs play important roles in the regulation of CI, and their expression levels are closely related to the damage and repair of CI [24,25]. In the present study, the CI-related data sets were searched through bioinformatics, downloaded from the GEO official website of the National Center for Biotechnology Information (NCBI), and the DEGs were screened.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of CI is complex, and it has been shown that it is related to excessive production of free radicals, the toxic effect of excitatory amino acids, intracellular calcium overload, inflammatory response, and autophagy [21][22][23]. miRNAs play important roles in the regulation of CI, and their expression levels are closely related to the damage and repair of CI [24,25]. In the present study, the CI-related data sets were searched through bioinformatics, downloaded from the GEO official website of the National Center for Biotechnology Information (NCBI), and the DEGs were screened.…”
Section: Discussionmentioning
confidence: 99%